2018
DOI: 10.1212/wnl.0000000000005256
|View full text |Cite
|
Sign up to set email alerts
|

Value of the central vein sign at 3T to differentiate MS from seropositive NMOSD

Abstract: This study provides Class III evidence that the CVS on 3T MRI accurately distinguishes patients with MS from those with seropositive NMOSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
68
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(71 citation statements)
references
References 31 publications
1
68
1
1
Order By: Relevance
“…Most existing studies focusing on the clinical value of the CVS for the differential diagnosis of MS included patients with an already known clinical diagnosis. 6,[8][9][10][11][12] One prior study investigated the diagnostic predictive value of the CVS in patients with possible MS, showing promising results. 28 However, this pilot study was done on a research 7T MRI scanner, and not all included patients experienced a neurological syndrome suggestive of MS.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most existing studies focusing on the clinical value of the CVS for the differential diagnosis of MS included patients with an already known clinical diagnosis. 6,[8][9][10][11][12] One prior study investigated the diagnostic predictive value of the CVS in patients with possible MS, showing promising results. 28 However, this pilot study was done on a research 7T MRI scanner, and not all included patients experienced a neurological syndrome suggestive of MS.…”
Section: Discussionmentioning
confidence: 99%
“…2,5 The presence of a vein at the center of brain white matter (WM) lesions, the "central vein sign" (CVS), is a specific feature of MS and can now be depicted at clinical MRI field strength using specialized gradient-echo MRI sequences. [5][6][7] Several studies have shown how this promising imaging biomarker can differentiate MS from other disorders, including migraine, 8,9 cerebral The "central vein sign" in patients with diagnostic "red flags" for multiple sclerosis: A prospective multicenter 3T study small vessel disease, 10 neuromyelitis optica, 11 Susac syndrome, 12 and primary or secondary vasculitis of the CNS, showing similar WM lesions on MRI. 6 However, most prior studies are retrospective.…”
Section: Introductionmentioning
confidence: 99%
“…This represents the imaging equivalent of inflammatory activity surrounding a vein on histology. 11 , 12 Studies in RRMS have shown its potential to differentiate RRMS from neuromyelitis optica 13 15 and SVD at 3 and 7T. 10 , 16 , 17 Studies at 7T showed PPMS had similar proportions of WMLs with central veins compared to RRMS.…”
mentioning
confidence: 99%
“…Our findings are particularly relevant considering that recent studies using manual CVS classification at clinical field strengths have shown potential for application of the CVS imaging biomarker in clinical practice . Importantly, the most recent international panel for MS diagnosis called for further research on this topic before considering inclusion of the CVS in future MS diagnostic criteria .…”
Section: Discussionmentioning
confidence: 81%
“…Indeed, pathology studies as early as the 19th century described the presence of a vein at the center of inflammatory lesions as a hallmark of the MS plaque . Today, the vein at the center of WM lesions can be imaged in vivo using optimized susceptibility‐based MRI sequences, and several studies have shown that the CVS can accurately distinguish MS from other disorders showing similar T2 hyperintensities on MRI . Results from a recent multicenter study suggest that the diagnostic performance of this CVS biomarker at clinical field strengths is highly dependent on the type of susceptibility‐based MRI sequence used .…”
Section: Introductionmentioning
confidence: 99%